Anti-Breast Cancer Activities of 8-Hydroxydaidzein by Targeting Breast Cancer Stem-Like Cells - Sadegh Rajabi; Maryam Shojaee; Ali Malmir; Mostafa Rezaei Tavirani; Shokoofe Noori (Frontiers Media S.A., 2020)
Purpose: Cancer stem cells (CSCs) play an important role in various stages of cancer development and therapy refractoriness. 8-Hydroxydaidzein (8-OHD) has revealed anti-cancer activity in different tumors. Accordingly, we aimed to assess the effects of 8-OHD on the suppression of breast cancer stem-like cells (BCSCs). Methods: The anti-proliferative and pro-apoptotic properties of 8-OHD were examined by MTS assay and flowcytometry. The expression levels of stemness markers and JAK2/STAT proteins were measured by quantitative real time-PCR (qRT-PCR) and western blotting, respectively. Results: 8-OHD significantly decreased three out of six stemness markers and remarkably reduced viability and induced apoptosis of spheroidal and parental cells compared to controls. Further experiments using CD95L, as a death ligand, and ZB4 antibody, as an extrinsic apoptotic pathway blocker, showed that 8-OHD induced apoptosis through the intrinsic pathway, proposing a mechanism by which 8-OHD triggers apoptosis. Results of western blot analysis also revealed a marked decline in the phosphorylation of JAK2 and STAT proteins. Conclusion: Our study, for the first time, elucidated an anti-BCSC activity for 8-OHD via decreasing stemness markers, inducing toxicity and stimulating apoptosis in these cells and parental cells. Our results also suggested a novel mechanism by which 8-OHD induces apoptosis in BCSCs.